Soteriological education in the system of professional and technical education - Totskyi, Ihor (National interest, 2024)
The article reveals the essence of soteriological education, aimed at the salvation of the human immortal soul, in the system of professional and technical education. The components of soteriological education are considered: cognitive, emotional, praxeological, motivational. Pedagogical conditions of soteriological education include the following: dialogic paradigm; person-oriented approach; activity of participants in the educational process; optimal and effective pedagogical (educational) environment; effective and regular pedagogical diagnosis of the level of spirituality (education) of pupils. The methods of soteriological education are defined as: the method of situational control; method of congruence (authenticity) of behavior; method of emotional resonance; personal orientation; method of personal identification; dialogue (polylogue); neurolinguistic programming and reprogramming. The main principles of soteriological education are described: systematicity, creative synergy, conformity to nature, voluntariness, systematicity and continuity of soteriological education, defining faith. The following are the forms of soteriological education: individual